Fenobody and RANbody-based sandwich enzyme-linked immunosorbent assay to detect Newcastle disease virus - Pinpin Ji; Jiahong Zhu; Xiaoxuan Li; Wenqi Fan; Qianqian Liu; Kun Wang; Jiakai Zhao; Yani Sun; Baoyuan Liu; En-Min Zhou; Qin Zhao (Journal of Nanobiotechnology, 2020)
Abstract Background Traditional sandwich enzyme-linked immunosorbent assay (ELISA) using polyclonal and monoclonal antibodies as reagents presents several drawbacks, including limited amounts, difficulty in permanent storage, and required use of a secondary antibody. Nanobodies can be easily expressed with different systems and fused with several tags in their tertiary structure by recombinant technology, thus offering an effective detection method for diagnostic purposes. Recently, the fenobody (ferritin-fused nanobody) and RANbody (nanobody-fused reporter) have been designed and derived from the nanobody for developing the diagnostic immunoassays. However, there was no report about developing the sandwich ELISA using the fenobody and RANbody as pairing reagents. Results A platform for developing a sandwich ELISA utilizing fenobody as the capture antibody and RANbody as the detection antibody was firstly designed in the study. Newcastle disease virus (NDV) was selected as the antigen, from which 13 NDV-specific nanobodies were screened from an immunized Bactrian camel. Then, 5 nanobodies were selected to produce fenobodies and RANbodies. The best pairing of fenobodies (NDV-fenobody-4, 800 ng/well) and RANbodies (NDV-RANbody-49, 1:10) was determined to develop the sandwich ELISA for detecting NDV. The detection limits of the assay were determined to be 22 of hemagglutination (HA) titers and 10 ng of purified NDV particles. Compared with two commercial assays, the developed assay shows higher sensitivity and specificity. Meanwhile, it exhibits 98.7% agreement with the HA test and can detect the reference NDV strains belonging to Class II but not Class I. Conclusions In the presented study, the 13 anti-NDV nanobodies binding the NDV particles were first produced. Then, for the first time, the sandwich ELISA to detect the NDV in the different samples has been developed using the fenobody and RANbody as reagents derived from the nanobodies. Considering the rapidly increasing generation of nanobodies, the platform can reduce the cost of production for the sandwich ELISA and be universally used to develop assays for detecting other antigens.